CREATE-ing capacity to take developmental crime prevention to scale: A community-based approach within a national framework. Issue 3 (September 2015) - Homel, Ross; Freiberg, Kate; Branch, Sara
Developmental crime prevention is founded on the long-term outcomes and economic efficiency of about 50 promising or model programs for fostering healthy child and youth development and for preventing crime. However, few if any of these programs have been successfully implemented on a large scale, a problem that is the focus of Type 2 (T2) Translation Research within prevention science. This paper describes one approach to building capacity for population-level community-based developmental prevention using the CREATE model that we developed as an outcome of the Pathways to Prevention Project that operated in a disadvantaged region of Brisbane between 2002 and 2011. CREATE is an acronym: C ollaborative; R elationships-driven; E arly in the pathway; A ccountable; T raining-focused; E vidence-driven. CREATE is being used to develop, in T2 Translation terms, a prevention support system (PSS) for the Communities for Children (CfC) program, a prevention delivery system that is operated by the Department of Social Services in 52 communities across Australia. The aim is to build the capacity for schools and community agencies to transcend system silos; foster ethical practices and respectful relationships; and deliver goal-directed, quantitatively evaluated, evidence-based resources that address the needs of families with complex needs, promote child wellbeing and prevent antisocial and criminal behaviours. The PSS combines web-based interactive electronic resources for schools and community agencies serving children in CfC communities with systems and processes established by project personnel called Collective Impact Facilitators who build the skills and knowledge of community coalitions to use the electronic resources and implement CREATE effectively. This capacity building exercise is being evaluated through a comprehensive array of pre- and post-measures of coalition functioning. The PSS integrates with national prevention infrastructure developed by DSS, including a Data Exchange System, an Expert Panel, and an Information Exchange.